2017
DOI: 10.1111/cid.12559
|View full text |Cite
|
Sign up to set email alerts
|

Computer guided sinus floor elevation through lateral window approach with simultaneous implant placement

Abstract: Within the limits of this study, computer guided sinus floor elevation showed promising results in accurately modifying the lateral window osteotomy and presents as a safe alternative to the standard technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Since then, numerous articles have been published describing various techniques for creating a sinus guide in a simple and predictable manner [18,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Among them, Osman et al (2018) conducted a comparison of the effectiveness of CAD-CAM-based antrostomy guides against the conventional lateral window approach technique, focusing on reducing the incidence of membrane perforation. The study showed that computer-guided sinus floor elevation exhibits promising results, effectively reducing perforation rate, with the potential to serve as a secure alternative to the standard technique [29].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, numerous articles have been published describing various techniques for creating a sinus guide in a simple and predictable manner [18,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Among them, Osman et al (2018) conducted a comparison of the effectiveness of CAD-CAM-based antrostomy guides against the conventional lateral window approach technique, focusing on reducing the incidence of membrane perforation. The study showed that computer-guided sinus floor elevation exhibits promising results, effectively reducing perforation rate, with the potential to serve as a secure alternative to the standard technique [29].…”
Section: Discussionmentioning
confidence: 99%
“…Other surgical guides have been proposed previously, either for achieving a less invasive approach at the donor site (Osman et al, 2018; De Stavola et al, 2015) or for improving the adaptation a bone block graft to the recipient site (Venet et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Low Window Technique involves a series of standardized surgical steps and is therefore easy to learn, repeatable, and less error-prone than the traditional freehand method. Because it involves the use of digital software to create a surgical template, it helps the surgeon perform osteotomies with precision [18][19][20][21]. The Low Window Technique allows easier access to the sinus and reduces invasiveness.…”
Section: Discussionmentioning
confidence: 99%